2015
DOI: 10.1002/2015ja021126
|View full text |Cite
|
Sign up to set email alerts
|

Causes of the longitudinal differences in the equatorial vertical E × B drift during the 2013 SSW period as simulated by the TIME‐GCM

Abstract: During stratospheric sudden warming (SSW) periods large changes in the low‐latitude vertical drift have been observed at Jicamarca as well as in other longitudinal sectors. In general, a strengthening of the daytime maximum vertical drift with a shift from prenoon to the afternoon is observed. During the January 2013 stratospheric warming significant longitudinal differences in the equatorial vertical drift were observed. At Jicamarca the previously reported SSW behavior prevails; however, no shift of the dayt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
123
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(138 citation statements)
references
References 91 publications
15
123
0
Order By: Relevance
“…This suggests that the lunitidal effect is not only stronger but also tend to be prominent among the four tidal components in the American sector than in the East Asian sector during SSWs, especially in major events. With Thermosphere-Ionosphere-Mesosphere Electrodynamics General Circulation Model simulation, Maute et al (2015) demonstrate that moderate geomagnetic conditions during the 2012-2013 SSW may introduce significant longitudinal differences in the daytime vertical drift enhancement between the American sector and the African sector. Qualitatively, the clarity of a TS signature indicates the relative importance of the TS-generating process compared to other driving factors.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This suggests that the lunitidal effect is not only stronger but also tend to be prominent among the four tidal components in the American sector than in the East Asian sector during SSWs, especially in major events. With Thermosphere-Ionosphere-Mesosphere Electrodynamics General Circulation Model simulation, Maute et al (2015) demonstrate that moderate geomagnetic conditions during the 2012-2013 SSW may introduce significant longitudinal differences in the daytime vertical drift enhancement between the American sector and the African sector. Qualitatively, the clarity of a TS signature indicates the relative importance of the TS-generating process compared to other driving factors.…”
Section: Discussionmentioning
confidence: 93%
“…Stening (2011) shows that the lunar tide of geomagnetic variations in the American sector (Huancayo, −12.0°S, −75.3°W) is much larger compared to the other sectors during SSWs. With Thermosphere-Ionosphere-Mesosphere Electrodynamics General Circulation Model, Maute et al (2015) indicate that the longitudinal difference of the TEC variations between American and African sectors may be caused by the different responses to the moderate geophysical conditions (Kp = 4), which accounts for approximately half of the daytime vertical drift increase in the American sector but is negligible in the African sector. Liu et al (2011) reported that the morning enhancement in TEC is significantly larger in the Peruvian sector than in the Asian sector, and the hemispheric asymmetry of the afternoon depletion is opposite in the two sectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SD nudging approaches of Maute et al () and J. C. Wang et al () were slightly different, but both constrained TIME‐GCM horizontal winds and neutral temperatures in an effort to study the lower atmospheric driving of the MLT and TI. Maute et al () constrained the zonal mean background atmosphere in the TIME‐GCM using hourly SD‐WACCM‐X output (i.e., WACCM‐X‐L116 was constrained using GEOS‐5), such that the zonal mean horizontal winds and neutral temperatures take the following form in the momentum and thermodynamic energy equations: trueX¯false(θ,z,tfalse)=false(1αζfalse(zfalse)false)trueX¯Modelfalse(θ,z,tfalse)+αζfalse(zfalse)trueX¯Datafalse(θ,z,tfalse), where θ = latitude, z=lnp0p or log pressure level ( p 0 =5 × 10 −7 hPa), t = time, trueX¯ represents zonal mean zonal ( trueu¯), and meridional ( truev¯) winds, and the zonal mean temperature ( trueT¯) from TIME‐GCM ( trueX¯Model) and WACCM‐X‐L116/GEOS5 ( trueX¯Data), where the overbar represents a zonal average dynamical field. The fraction, α , is used to determine the relaxation time following Smith, Pedatella, et al (), which in the Maute et al () case is assumed to be 1.…”
Section: Model Simulations Data Sets and Methodologymentioning
confidence: 99%
“…The response of the thermosphere to geomagnetic forcing depends on the prior thermospheric conditions, which are largely determined by driving from below . Maute et al (2015) recently addressed the question with simulations representative of the conditions during a sudden stratospheric warming (SSW) in 2013, during which geomagnetic and tidal forcing acted at the same time. Tidal forcing, which originates from below the T-I, was found to create comparable effects to geomagnetic forcing, although the relative influences varied with longitude.…”
Section: Coupling Of the Thermosphere-ionosphere To Regions Above Andmentioning
confidence: 99%